ANALISIS YURIDIS PENERAPAN SANKSI PIDANA TERHADAP OKNUM PEJABAT PEMERINTAH DESA DALAM TINDAK PIDANA KORUPSI ALOKASI ANGGARAN DESA - Yolanda Oktavia; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Abuse of authority which has implications for the most criminal acts of corruption because the perpetrators are not only from people who stand or stand strategically in the government and state system located in the Capital City of the State. Therefore this thesis discusses the juridical analysis of the implementation of criminal sanctions against individual village government officials in the crime of village budget corruption.This type of research used in this research is to use normative research, namely the absence of a procedure between the judge's decision and the existing rules in the Corruption Eradication Act. Sources of data used, namely: primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques be it all literature books, whether primary, secondary or tertiary legal materials related to research problems. This study was analyzed using qualitative analysis.The results of this thesis research are first, the perpetrators of criminal acts of corruption committed by the village head should be charged with Article 3 of the Corruption Eradication Law, because it is very clear in Article 3 that there is an